Spatially fractionated radiotherapy (SFRT) targeting the hypoxic tumor segment for the intentional induction of non-targeted effects: An in silico study to exploit a new treatment paradigm. (June 2020) - Massaccesi, M.; Boldrini, L.; Piras, A.; Stimato, G.; Quaranta, F.; Azario, L.; Mattiucci, G.C.; Valentini, V.
Highlights: Optimizing the dose prescription of SBRT-PATHY may spare tumor infiltrating immune cells. Dose prescription method may vary according to the lesion and its hypoxic segment. SBRT-PATHY may be technically feasible also in non bulky lesions. Abstract: Introduction: The possibility of intentionally triggering non targeted effects (NTEs) using spatially fractionated radiotherapy (SFRT) alone or combined with immunotherapy is an intriguing and fascinating area of research. Among different techniques for SFRT, stereotactic body radiotherapy targeting exclusively the central hypoxic segment of bulky tumors, (SBRT-PATHY) might trigger immunogenic cell death more efficiently. This in silico study aims to identify the best possible dosimetric trade-off for prescribing SFRT with volumetric modulated arc (VMAT) based stereotactic radiotherapy (SRT). Material and methods: Eight spherical volumes defined "Gross Tumor Volumes" (GTVs) were generated with diameters of 3–10 cm (with incremental steps of 1 cm), simulating tumor lesions. The inner third part of each GTV (GTVcentral ) was selected to simulate the central hypoxic area and a ring structure was derived around it to simulate the tumor periphery (GTVperipheral ). Volumetric modulated arc radiation treatment (VMAT) plans were calculated to deliver a single fraction of 10 Gy to each GTVcentral with different dose prescription methods: target mean and isodose driven (40, 50, 60, 70, 80 and 90%). The volume of GTVperipheral receiving less than 2 Gy was recorded as dosimetric performance indicator. Results: 56 possible dosimetric scenarios were analyzed. The largest percentage of GTVperipheral spared from the dose of 2 Gy was achieved with dose prescription methods to the 70% isodose line for lesions smaller than 6 cm (range 42.9–48.4%) and to the target mean for larger ones (range 52.9–64.5%). Conclusions: Optimizing the dose prescription method may reduce the dose to tumor periphery in VMAT-based SFRT, thus potentially sparing tumor infiltrating immune cells. The optimal method may vary according to the size of the lesion. This should be taken into account when designing prospective trials using SFRT.